문제

I have to transform the following grammar into a non left recursive grammar:

S → aSb | bAS

A → AaA | bAA | AAa | bAb

This is what I came up with:

A → bAAA’| bAbA’

A’ → aAA’| AaA’| ε

S → aSb | bAS

As far as I can tell, there is no more left recursion because none of the leftmost symbols on the RHS are the same as the nonterminal on the left. However, assuming S is the starting symbol, there is still infinite recursion because A calls itself repeatedly. Is this expected? Or did I derive the non left recursive grammar incorrectly?

올바른 솔루션이 없습니다

라이센스 : CC-BY-SA ~와 함께 속성
제휴하지 않습니다 cs.stackexchange
scroll top